Design of neonatal dried blood spot immunoassays for two novel biomarkers - Valtonen, Salla (My University, 2018)
Spinal muscular atrophy (SMA) is a genetic disorder that leads to muscle weakness and atrophy and, in the most severe form, death before the age of two. It is caused by lack of survival of motor neuron (SMN) protein. Congenital heart defects are malformations caused by abnormal development before birth. They range from asymptomatic to fatal and can be detected by measuring the plasma concentration of N-terminal pro-B-type natriuretic peptide (NT-proBNP). The aim of this study was to develop immunometric immunoassays that could detect SMN and NT-proBNP from neonatal dried blood spot (DBS) samples using an automated laboratory analyzer, to detect, respectively, the SMA phenotype or congenital heart defects at an early stage. Capture antibodies were attached to a solid surface via adsorption coating or biotin-streptavidin interaction. Tracer antibodies were labeled with N1-Eu- or N3-Eu-chelate. From DBS samples, 3.2 mm disks were punched into the microtiter wells. The assays were performed either sequentially on different instruments or by the GSP instrument. SMN detection requires lysis of the blood cells. Using optimized lysis and assay protocols, the SMN concentration measured from DBS samples of healthy individuals was at most 4.3 ng/ml, whereas a concentration range of 8.1-11 ng/ml was acquired from whole blood samples. The assay was functional but lacks sensitivity for detecting the SMN levels of SMA-positive DBS samples. NT-proBNP was assayed from DBS samples with sufficient sensitivity, and the assay was transferred to the GSP instrument. The NT-proBNP concentrations of 83 neonatal DBS samples were measured to be 580-10 800 pg/ml and fitted a log-normal distribution. Clinical samples would be required to evaluate the diagnostic value of this assay.
Keywords: neonatal diagnostics, spinal muscular atrophy, survival of motor neuron, congenital heart disease, NT-proBNP